2006
DOI: 10.1163/156854006776952892
|View full text |Cite
|
Sign up to set email alerts
|

Range extension and establishment of a breeding population of the Asiatic copepod, Pseudodiaptomus marinus Sato, 1913 (Calanoida, Pseudodiaptomidae) in Todos Santos Bay, Baja California, Mexico

Abstract: The Asiatic copepod, Pseudodiaptomus marinus is recorded for the first time in Todos Santos Bay, Baja California. The first specimens were collected near a newly constructed marina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…During the same time, P. marinus was recorded even farther north on the coast of California (Orsi & Walter, 1991) and was still present among the numerous alien species of the San Francisco estuary 10 years later (Choi et al, 2005). In 1998, P. marinus was detected for the first time in the coastal area of Todos Santos Bay (Baja California, Mexico), and further surveys in 2002 confirmed that the species was established in this area (Jiménez-Pérez & Castro-Longoria, 2006).…”
Section: Biogeography Of Pseudodiaptomus Marinusmentioning
confidence: 96%
“…During the same time, P. marinus was recorded even farther north on the coast of California (Orsi & Walter, 1991) and was still present among the numerous alien species of the San Francisco estuary 10 years later (Choi et al, 2005). In 1998, P. marinus was detected for the first time in the coastal area of Todos Santos Bay (Baja California, Mexico), and further surveys in 2002 confirmed that the species was established in this area (Jiménez-Pérez & Castro-Longoria, 2006).…”
Section: Biogeography Of Pseudodiaptomus Marinusmentioning
confidence: 96%